Heat-sealable paper fabricated using a latex coating based on modified natural rubber filled with gelatin - Rattanawadee Ninjan; Bencha Thongnuanchan; Natinee Lopattananon; Subhan Salaeh; Phakawat Thongnuanchan; Pornsuwan Buangam (eXPRESS Polymer Letters)
Research into sustainable packaging materials has gained increasing importance due to the pressing environmental concerns related to plastic waste. The present study focused on developing a sustainable paper coating based on modified natural rubber (NR) latex filled with gelatin (GT). The graft copolymer latex of NR and poly(vinylbenzyl chloride) bearing quaternary ammonium groups, abbreviated as NR-g-QPVBC, was first synthesized. GT was then incorporated into the latex, and the combination of these materials resulted in a heat-sealable film with good tensile properties and a water barrier. The ionic crosslinking of the latex film was achieved by the reaction with ethylenediaminetetraacetic acid (EDTA). Heat-sealing studies of the NR-g-QPVBC latex film filled with GT (NR-g-QPVBC/GT) revealed its heat-sealability at 160 °C. Scanning electron microscope (SEM) analysis further confirmed the diffusion of the chains across the interface during heat sealing. Dip coating was a method for depositing latex film on kraft paper. The paper coated with the NR-g-QPVBC/GT latex showed a significant increase in dry and wet-tensile strength compared to the uncoated paper. The sealing process was optimized to achieve a heat-seal strength of 755.31 N/m at a dwell time of 3 s and a temperature of 160 °C. The research's practical application was demonstrated by transforming the coated paper into various heat-sealable bags using a handheld bag sealer.